DETERMINATION OF DIMENSIONAL PARAMETERS FOR ANNULAR CONCENTRATOR OF ULTRASONIC SYSTEM - V. P. Lugovoi; I. V. Lugovoi (Наука и техника)
Conventional ultrasonic systems contain concentrators of longitudinal type to amplify and transfer vibrations to a tool. Along with them, elastic rings with variable cross section thickness can be used effectively as concentrators for ultrasonic vibrations of acoustic systems. Their practical application requires a scientifically substantiated methodology for determination of geometric parameters. The paper provides substantiation of the method used to determine dimensions of annular concentrators with a variable cross section which can enhance effectiveness of the ultrasound equipment while performing various technological tasks. Visual analysis of acoustic waves radiated by annular concentrators has shown that the most intensive vibrations are produced in the most thin sections. Computer simulation of oscillations in rings with an external diameter of 50 mm and a variable cross section has demonstrated that the largest increase of vibration amplitude is achieved at a certain ratio of ring thicknesses and diameters. An analysis of numerical values for amplication factor of vibrational amplitude Kд has revealed that there is a limit boundary for the ratio of ring wall thicknesses which, in its turn, depends on the ratio of ring outer and inner diameters at certain values of hole axis eccentricity. The ratio of diameters is expressed quantitatively by the coefficient Kд. An analysis of the results concerning numerical calculations of amplitude amplification factor performed for the specified model of the ring having 50 mm diameter have illustrated that this ratio should lie between 1.3 > Kд > 1.15. The obtained results can be used in ultrasonic devices with annular concentrators in order to perform various technological tasks.